Regioselective Hydroperoxylation of Aziridines and Epoxides Only with Aqueous Hydrogen Peroxide. Issue 2 (25th October 2021) - Saleh, SK Abu; Hazra, Atanu; Hajra, Saumen
Abstract: A catalyst and organic solvent‐free regioselective hydroperoxylation of aziridines and epoxides, including spiroaziridine‐ and spiroepoxy oxindoles have been explored with commercially available 50% aq. H2 O2 . This method provides an access to secondary benzylic β‐hydroperoxy amines and ‐alcohols and tertiary 3‐hydroperoxy oxindoles. The protocol is also applicable to the less reactive alkyl aziridines. Furthermore, an acid‐catalyzed Kornblum‐DeLaMare type rearrangement of secondary benzylic hydroperoxide has also been revealed to afford amino‐ and hydroxyl ketones. Abstract :